Synthesis and Evaluation of a Polycaprolactone-methoxy-Polyethyleneglycol Copolymer Nano-system for Curcumin and Tacrolimus Release: Drug Delivery Nano-system - Shahifar, Anita; Bagheri, Hamed; Namnabat, Sogol (Iranian Journal of Pharmaceutical Sciences, 2023)
Conventional drug delivery methods are not highly efficient due to low bioavailability, poor absorption, and inadequate retention time of some medications. In addition, to achieve the appropriate therapeutic effect, a higher dosage of drugs might be administrated, which may result in undesired side effects. In order to overcome these challenges, utilizing drug delivery systems such as micelles could be beneficial. Micelles are amphiphilic compounds with a hydrophilic shell and a hydrophobic core. Micelles could encapsulate hydrophobic drugs such as Curcumin and tacrolimus, anti-inflammatory and immunosuppressive agents, respectively, and improve their bioavailability. This study synthesized a Methoxy-Polyethyleneglycol-Polycaprolactone biodegradable nano-system by precipitation method for curcumin and tacrolimus encapsulation. Afterward, micelles were characterized for size, morphology, drug loading capacity, and drug release. As a result, the average molecular weight of the copolymer was 36744 g/mol. The nano-system size was analyzed using Dynamic light scattering and Atomic force microscopy tests, resulting in 137.6 nm and 37.9 nm, respectively. In addition, the drug loading efficiency was 42.06%, and after 96 hours, about 0.7mg of Curcumin was released while no Tacrolimus was detected. Since Tacrolimus is retained in the system, we can conclude that this system is not suitable for the simultaneous release of two drugs.